The Strategic Character of the Cooperation Relationship Between the EU and the BRIC Countries - Iulia Monica Oehler-Şincai (Romanian Journal of European Affairs, 2011)
Brazil, the Russian Federation, India and China (coined under the acronym BRIC at the end of 2001) are alongside the United States of America (USA), Canada, Japan, Mexico and South Africa the strategic partners of the European Union (EU). Although the relationships between the EU and each of the four largest emerging economies in the world have a common backbone – the bilateral trade and investment flows – each one bears its own particularities. In this article, our purpose is to explore the strategic partnerships between the EU and the BRIC countries with emphasis on the economic pillar of the EU-BRIC cooperation framework. In our investigation, we will start with the analysis of the “BRIC mechanism”, continue with a short presentation of the particularities of the individual relationships between the EU and each BRIC country, and conclude with emphasising the EU role in the process of modernization of these economies.